The Joint Effect of the Availability of Choice and Perceived Behavioral Control on Intention to Use Taxi Service - Kaewchankha, Wasin; Sakworawich, Arnond (Journal of Applied Statistics and Information Technology, 2016)
People usually prefer to more choices and stronger sense of control. However, the result of this study clearly found that perceived behavioral control is much more important than availability of choice to predict intention to use. Specifically, consumers with lower level of perceived behavioral control will even exhibit lower level of behavioral intention if they possess more availability of choice than less choice. Moreover, we also found that male consumers exhibit higher behavioral intention than female when they possess higher perceived behavioral control. The roles of control and choice in service marketing are discussed